Do home adaptation interventions help to reduce emergency fall admissions? A national longitudinal data-linkage study of 657, 536 older adults living in Wales (UK) between 2010 and 2017. (18th October 2021) - Hollinghurst, Joe; Daniels, Helen; Fry, Richard; Akbari, Ashley; Rodgers, Sarah; Watkins, Alan; Hillcoat-Nallétamby, Sarah; Williams, Neil; Nikolova, Silviya; Meads, David; Clegg, Andy
Abstract: Background: falls are common in older people, but evidence for the effectiveness of preventative home adaptations is limited. Aim: determine whether a national home adaptation service, Care&Repair Cymru (C&RC), identified individuals at risk of falls occurring at home and reduced the likelihood of falls. Study Design: retrospective longitudinal controlled non-randomised intervention cohort study. Setting: our cohort consisted of 657, 536 individuals aged 60+ living in Wales (UK) between 1 January 2010 and 31 December 2017. About 123, 729 individuals received a home adaptation service. Methods: we created a dataset with up to 41 quarterly observations per person. For each quarter, we observed if a fall occurred at home that resulted in either an emergency department or an emergency hospital admission. We analysed the data using multilevel logistic regression. Results: compared to the control group, C&RC clients had higher odds of falling, with an odds ratio (OR [95% confidence interval]) of 1.93 [1.87, 2.00]. Falls odds was higher for females (1.44 [1.42, 1.46]), older age (1.07 [1.07, 1.07]), increased frailty (mild 1.57 [1.55, 1.60], moderate 2.31 [2.26, 2.35], severe 3.05 [2.96, 3.13]), and deprivation (most deprived compared to least: 1.16 [1.13, 1.19]). Client fall odds decreased post-intervention; OR 0.97 [0.96, 0.97] per quarter. Regional variation existed for falls (5.8%), with most variation at the individual level (31.3%). Conclusions: C&RC identified people more likely to have an emergency fall admission occurring at home, and their service reduced the odds of falling post-intervention. Service provisioning should meet the needs of an individual and need varies by personal and regional circumstance.